The reasons of love - Frankfurt, Harry G., 1929-2023 (Princeton, N.J. : Princeton University Press, 2006)
This beautifully written book by one of the world's leading moral philosophers argues that the key to a fulfilled life is to pursue wholeheartedly what one cares about, that love is the most authoritative form of caring, and that the purest form of love is, in a complicated way, self-love. Harry Frankfurt writes that it is through caring that we infuse the world with meaning. Caring provides us with stable ambitions and concerns; it shapes the framework of aims and interests within which we lead our lives. The most basic and essential question for a person to raise about the conduct of his or.
1. Question: "How Should We Live?" -- 2. On Love, and Its Reasons -- 3. Dear Self.
Includes bibliographical references.
Print version record.
JSTOR
Keywords: Liebe, ...; Practical reason; Love; Love; Raison pratique; Amour; love (emotion); FAMILY & RELATIONSHIPS -- Interpersonal Relations; PHILOSOPHY -- Ethics & Moral Philosophy; Love; Practical reason; Praktische Vernunft; Ethik; Selbstliebe; Liefde